Lithium iron phosphate positive electrode material and preparation method thereof

By using fatty alcohol polyoxyethylene ether phosphate as a carbon source, the carbon coating method of lithium iron phosphate positive electrode material is optimized, and the existing materials are insufficient in the fields of low temperature and high power are solved, and a high capacity and small particle size lithium iron phosphate positive electrode material is prepared, which improves the energy efficiency and market adaptability of the battery.

CN119905578APending Publication Date: 2025-04-29广州融捷能源科技有限公司

Patent Information

Application Number
CN202411988301.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing lithium iron phosphate positive electrode materials have low performance in the fields of low-temperature energy storage and high-power, and the preparation method has problems such as high cost, complex process and insufficient performance.

Method used

By using fatty alcohol polyoxyethylene ether phosphate as the carbon source, the carbon coating method of lithium iron phosphate positive electrode material is optimized, and particle growth is hindered during the sintering process, and a small particle size and high capacity lithium iron phosphate positive electrode material is prepared.

Benefits of technology

The preparation of lithium iron phosphate positive electrode material mainly distributed in small particles has been achieved, which improves discharge energy and energy efficiency, and adapts to the demand of the energy storage market.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905578A_ABST
    Figure CN119905578A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate positive electrode material preparation method, which comprises: 1, adding high polyphosphoric acid and fatty alcohol ether polyoxyethylene ether into a reaction kettle, uniformly mixing, and carrying out a reaction for 2-4 h at a temperature of 70-90 DEG C to obtain fatty alcohol polyoxyethylene ether phosphate; 2, adding iron phosphate, a lithium source, a conductive agent, a metal compound and the fatty alcohol-polyoxyethylene ether phosphate into water, and carrying out ball milling to form mixed slurry; and 3, sequentially carrying out spray drying, sintering and crushing on the mixed slurry to obtain the lithium iron phosphate positive electrode material. Compared with the prior art, the lithium iron phosphate positive electrode material has the advantages that the carbon coating mode of the lithium iron phosphate positive electrode material is optimized by adopting the scheme of taking the fatty alcohol polyoxyethylene ether phosphate as the carbon source, relatively large steric hindrance is generated by decomposition of the carbon source in the sintering process, and growth of lithium iron phosphate particles is hindered; and the lithium iron phosphate positive electrode material with small particle distribution as a main component is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Phosphate-based cathode materials such as lithium iron phosphate have the advantages of abundant raw materials, low cost and high mass specific capacity, and are currently the preferred cathode materials for energy storage lithium-ion batteries. However, the phosphate-based cathode materials themselves have low lithium ion diffusion coefficients and electronic conductivity, which affects their performance and service life in low-temperature energy storage and high-power fields. In the existing preparation methods or processes of phosphate-based lithium iron phosphate, most of them use modification methods such as nano-sizing, metal doping and carbon coating to improve the capacity, rate, low temperature and cycle life of lithium iron phosphate during application.

[0003] Adjusting the morphology of lithium iron phosphate through processes such as hydrothermal method and achieving nano-sizing can shorten the lithium ion transmission distance to a certain extent and improve the diffusion efficiency of lithium ions. However, the hydrothermal method has the disadvantages of high cost and complex process, and nano-sized particles have low compaction density and low gram capacity, which is not conducive to marketization.

[0004] Carbon coating is one of the conventional methods to improve the performance of lithium iron phosphate, but it will reduce the energy density of lithium iron phosphate batteries to a certain extent. As the amount of coating increases, the reduced carbon in the sintering process will further suppress the growth of lithium iron phosphate primary particles, resulting in a further decrease in compaction density, which will reduce the energy density of lithium iron phosphate batteries and is not conducive to market promotion.

[0005] At present, the shortcomings of ion doping are mainly small amounts of single metal ion doping, and simple metal oxide structure dopants often cannot achieve good performance improvement; increasing the doping dosage will increase the cost and increase the risk of lithium iron phosphate forming an impure phase that affects the crystal stability; and the use of doping elements such as rare earth or precious metals is often not conducive to the marketization of products due to high costs. Therefore, there is still room for adjustment and improvement in the selection of metal ions, the form of metal compounds, and the dosage of ion doping.

[0006] In view of the above mainstream lithium iron phosphate improvement methods, lithium iron phosphate manufacturers generally combine multiple grinding and multiple firing, blending and other methods to adjust the particle morphology and particle grading, to a certain extent balance the comprehensive performance such as energy density, rate low temperature, cycle life and energy efficiency, so as to adapt to market changes. However, multiple grinding and multiple firing are difficult to break through in the synthesis process and cost control, while blending is difficult to select suitable small particle blending materials.

[0007] In view of the above-mentioned defects of the current lithium iron phosphate positive electrode materials, it is indeed necessary to provide a technical solution to the above-mentioned problems. Summary of the invention

[0008] The object of the present invention is to provide a method for preparing a lithium iron phosphate positive electrode material, by which a lithium iron phosphate positive electrode material with high capacity and small particle size can be prepared.

[0009] In order to achieve this object, the present invention provides the following scheme:

[0010] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:

[0011] Step 1: Add high polyphosphoric acid and fatty alcohol ether polyoxyethylene ether into a reaction kettle and mix well, and react at 70-90° C. for 2-4 hours to obtain fatty alcohol polyoxyethylene ether phosphate;

[0012] Step 2: adding iron phosphate, a lithium source, a conductive agent, a metal compound and the fatty alcohol polyoxyethylene ether phosphate into water for ball milling to form a mixed slurry;

[0013] Step three: spray-drying, sintering and crushing the mixed slurry in sequence to obtain a lithium iron phosphate positive electrode material.

[0014] Preferably, in the step 1, the degree of polymerization of the high polyphosphoric acid is 3 to 5.

[0015] Preferably, in the step 1, the number of carbon atoms in the carbon chain of the fatty alcohol polyoxyethylene ether is 10-15.

[0016] Preferably, in the step 2, the mass ratio of the fatty alcohol polyoxyethylene ether phosphate to the iron phosphate is 10-15%.

[0017] The present invention also provides a lithium iron phosphate positive electrode material, comprising a lithium iron phosphate matrix and a carbon coating layer coated on the surface of the lithium iron phosphate matrix, wherein the carbon coating layer accounts for 1.1-1.9% of the total mass of the lithium iron phosphate positive electrode material.

[0018] Preferably, the particle size D50 of the lithium iron phosphate positive electrode material is 0.2-0.45 μm.

[0019] Preferably, the specific surface area of ​​the lithium iron phosphate positive electrode material is 11 to 18 g / cm 2 .

[0020] The present invention also provides a positive electrode sheet, comprising a positive electrode material, a conductive agent and a binder, wherein the positive electrode material comprises the above-mentioned lithium iron phosphate positive electrode material.

[0021] The present invention also provides a secondary battery, comprising a diaphragm, a negative electrode sheet, an electrolyte, a battery casing and the positive electrode sheet mentioned above.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention optimizes the carbon coating method of lithium iron phosphate positive electrode materials by using fatty alcohol polyoxyethylene ether phosphate as a carbon source. The decomposition of the carbon source during the sintering process produces a large steric hindrance, which hinders the growth of lithium iron phosphate particles, thereby preparing a lithium iron phosphate positive electrode material with a mainly small particle distribution.

[0024] (2) The lithium iron phosphate positive electrode material prepared by the preparation method of the present invention is small-particle, which is significantly better than large-particle lithium iron phosphate positive electrode material in overcoming kinetic effects. Increasing the proportion of small-particle lithium iron phosphate positive electrode material in the positive electrode active material can effectively increase the discharge energy, thereby achieving energy efficiency improvement and making the product more adaptable to the needs of the energy storage market. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM test image of the lithium iron phosphate positive electrode material of Example 1 of the present invention;

[0026] Figure 2 It is a particle size distribution curve diagram of the lithium iron phosphate positive electrode materials of Examples 1 and 8 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0027] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] According to a first aspect of the present invention, a method for preparing a lithium iron phosphate positive electrode material is provided, comprising the following steps:

[0029] Step 1: Add high polyphosphoric acid and fatty alcohol ether polyoxyethylene ether into a reaction kettle and mix well, react at 70-90° C. for 2-4 hours to obtain fatty alcohol polyoxyethylene ether phosphate; this step requires ensuring that the fatty alcohol ether polyoxyethylene ether completely consumes the high polyphosphoric acid in excess.

[0030] Step 2: adding iron phosphate, lithium source, conductive agent, metal compound and fatty alcohol polyoxyethylene ether phosphate into water for ball milling to form a mixed slurry;

[0031] Step 3: spray-dry, sinter and crush the mixed slurry in sequence to obtain lithium iron phosphate positive electrode material.

[0032] Among them, the present invention optimizes the carbon coating method of lithium iron phosphate positive electrode material by adopting fatty alcohol polyoxyethylene ether phosphate as the carbon source. The decomposition of the carbon source during the sintering process produces a large steric hindrance, which hinders the growth of lithium iron phosphate particles, and prepares a lithium iron phosphate positive electrode material with a mainly small particle distribution.

[0033] When the positive electrode active material is subsequently prepared, the mixing technology is used in combination with conventional high-compaction materials to achieve a combination of large and small particles with specialized small particles as the main component, thereby ensuring the gram capacity without reducing the compaction density.

[0034] In one embodiment of the present invention, the metal compound is one or a mixture of two or more of titanium, vanadium and niobium. Preferably, the metal compound is one or a combination of titanium dioxide.

[0035] Furthermore, the amount of the metal compound accounts for 0.8-2.2% of the amount of the iron phosphate. Further preferably, the amount of the metal compound accounts for 1.1-1.7% of the amount of the iron phosphate. The addition of the metal compound is conducive to more uniform sintering of the particles.

[0036] In one embodiment of the present invention, the conductive agent is one or more of carbon nanotubes, graphene, carbon nanotubes, and conductive carbon black. More preferably, the conductive agent is one or a mixture of carbon nanotubes and graphene.

[0037] Furthermore, the amount of the conductive agent used is 0.1 to 0.75% of the mass of the iron phosphate used.

[0038] In one embodiment of the present invention, the particle size of the ball milled in step 2 is 0.29-0.33 μm.

[0039] In one embodiment of the present invention, the solid content of the mixed slurry is 30-40%.

[0040] In one embodiment of the present invention, the iron-phosphorus ratio of the iron phosphate is 0.978-0.985, and the specific surface area is 10-15m 2 g -1 More preferably, the iron-phosphorus ratio is 0.980-0.984, and the specific surface area is 12-14 m 2 g -1 Iron phosphate with a high iron-phosphorus ratio is beneficial to the preparation of high-gram capacity lithium iron and also provides sufficient space for the addition of phosphorus supplements.

[0041] In one embodiment of the present invention, the lithium source is battery-grade lithium carbonate, and the molar ratio of lithium in the lithium source to iron in the iron phosphate is 1:1.015-1.050.

[0042] In one embodiment of the present invention, the spray drying inlet temperature is 240-280° C., the outlet temperature is 100-110° C., and the spray granulation particle size D50 is controlled at 5-30 μm.

[0043] In one embodiment of the present invention, the sintering conditions in step 3 are: under nitrogen protection, with an oxygen content of less than 20ppm, a furnace pressure greater than 20Pa in the sintering furnace, a pot thickness of 3-6cm, and a total sintering time of 14-16 hours. Specifically, the precursor obtained after spray drying is heated to 700-750°C for 5-6 hours, then kept at this temperature for 9-10 hours, and naturally cooled to less than 50°C to obtain a sintered material.

[0044] In one embodiment according to the present invention, the screening in step three is through a 400-mesh sieve.

[0045] Fatty alcohol polyoxyethylene ether phosphate is prepared by esterifying high polyphosphoric acid with fatty alcohol polyoxyethylene ether.

[0046] Among them, the ethylene oxide polymerization degree of fatty alcohol polyoxyethylene ether is related to the critical micelle state formed by iron phosphate during the grinding process. Increasing the ethylene oxide polymerization degree is conducive to the formation of the critical micelle state, thereby more effectively improving the grinding effect; therefore, the generally selected ethylene oxide polymerization degree is 10 to 20.

[0047] The ethylene oxide addition number of fatty alcohol polyoxyethylene ether phosphate is between 10 and 20; the carbon chain is a straight chain hydroxyl group, and the carbon number of the carbon chain is between 10 and 15. If the ethylene oxide addition number is too low, it will not be water-soluble, and if it is too high, the cost will increase significantly.

[0048] In one embodiment according to the present invention, in step 1, the degree of polymerization of high polyphosphoric acid is 3 to 5. When the degree of polymerization of high polyphosphoric acid is 3 to 5, it is beneficial to improve the esterification rate, but when the degree of polymerization is too high, the consistency of the degree of polymerization of high polyphosphoric acid is reduced, and the consistency of the esterification effect is reduced. More preferably, the degree of polymerization is 4.

[0049] In one embodiment of the present invention, in step 1, the number of carbon atoms in the carbon chain of the fatty alcohol polyoxyethylene ether is 10 to 15. The number of carbon atoms in the carbon chain of the fatty alcohol polyoxyethylene ether is related to the steric hindrance formed during the sintering process. When the number of carbon atoms is 10 to 15, the steric hindrance provided during the sintering process can be effectively increased, the growth of the primary particles of lithium iron phosphate can be effectively controlled, and the realization of nano-crystallization can be achieved.

[0050] In one embodiment of the present invention, in step 2, the mass ratio of fatty alcohol polyoxyethylene ether phosphate to iron phosphate is 10-15%. The amount of carbon source used as a phosphorus supplement should not be too high; and a too low iron-phosphorus molar ratio may lead to excessive lithium phosphide and insufficient crystallinity of iron lithium after sintering. Preferably, the iron-phosphorus molar ratio of iron phosphate and fatty alcohol polyoxyethylene ether phosphate is not less than 96%.

[0051] In the process of preparing the mixed slurry, fatty alcohol polyoxyethylene ether phosphate can effectively increase the viscosity of the slurry, thereby increasing the shear stress on the iron phosphate during the grinding process and improving the grinding effect; in addition, fatty alcohol polyoxyethylene ether phosphate will form a critical micelle state on the surface of the iron phosphate under its wetting and dispersing force, which hinders the agglomeration of iron phosphate particles at the microscopic level, thereby making the iron phosphate more fully ground and improving the grinding effect; iron phosphate can achieve a smaller grinding particle size and the grinding efficiency is effectively improved, making the preparation process more suitable for the production of small-particle lithium iron phosphate positive electrode materials, and saving production costs and production cycles, making it more conducive to industrialization.

[0052] In addition, fatty alcohol polyoxyethylene ether phosphate decomposes during the preparation process. Since P is mixed with the carbon source, it is beneficial to form a tighter and more complete lithium iron phosphate coating on the surface of the primary particles. At the same time, the force generated by this process can effectively hinder the fusion between the primary particles, further preventing the growth of the primary particles.

[0053] Since the growth of primary particles can be effectively inhibited, there is no need to prevent the growth of particles by lowering the sintering temperature, thereby avoiding the problem of excessive specific surface area and powder resistivity caused by insufficient density and uniformity of lithium iron phosphate carbon coating due to insufficient sintering temperature; and the problem of insufficient capacity and rate performance caused by insufficient crystallinity of lithium iron phosphate. Small-particle lithium iron phosphate positive electrode materials can be successfully prepared.

[0054] According to the second aspect of the present invention, a lithium iron phosphate positive electrode material is further provided. The lithium iron phosphate positive electrode material is prepared by the above-mentioned preparation method.

[0055] In one embodiment according to the present invention, a lithium iron phosphate substrate and a carbon coating layer coated on the surface of the lithium iron phosphate substrate are included, and the carbon coating layer accounts for 1.1-1.9% of the total mass of the lithium iron phosphate positive electrode material. Further preferably, the coated carbon accounts for 1.2-1.5% of the total mass of the lithium iron phosphate positive electrode material. Carbon materials have good electrical conductivity, and can form a conductive network when coated on the surface of lithium iron phosphate particles, significantly improving the electronic conductivity of the material; it can also promote the conduction of lithium ions and reduce the resistance to ion migration, thereby improving the rate performance of the battery. If the amount of carbon coating is too low, an effective conductive network cannot be formed, which will cause the electronic conductivity of the material to decrease, thereby affecting the charge and discharge performance of the battery. On the contrary, if the amount of carbon coating is too high, although the conductivity can be improved, too much carbon will occupy the position of the active material, reduce the content of the active material, and also affect the performance of the battery.

[0056] In one embodiment of the present invention, the particle size D50 of the lithium iron phosphate positive electrode material is 0.2-0.8 μm, and more preferably 0.2-0.45 μm.

[0057] In one embodiment of the present invention, the specific surface area of ​​the lithium iron phosphate positive electrode material is 11-18 g / cm 2 .

[0058] The lithium iron phosphate positive electrode material has regular morphology, complete carbon coating, high degree of nano-sizing, simple processing, and excellent gram capacity and energy efficiency performance.

[0059] The lithium iron phosphate positive electrode material of the present invention is small-particle, and is significantly better than large-particle lithium iron phosphate positive electrode material in overcoming kinetic influences. Increasing the proportion of small-particle lithium iron phosphate positive electrode material in the positive electrode active material can effectively increase the discharge energy, thereby achieving energy efficiency improvement and making the product more adaptable to the needs of the energy storage market.

[0060] In the third aspect of the present invention, a positive electrode sheet is also provided, comprising a positive electrode material, a conductive agent and a binder, wherein the positive electrode material comprises the above-mentioned lithium iron phosphate positive electrode material. When using the small-particle lithium iron phosphate positive electrode material of the present invention, a mixed scheme is often adopted, mainly to address the common problem that the current large and small particle grading scheme of high-pressure compacted lithium iron material has an insufficient proportion of small particles. The positive electrode active material of the battery formed by adding the small-particle lithium iron phosphate positive electrode material of the present invention to the conventional lithium iron phosphate positive electrode material can effectively form a large and small particle grading scheme dominated by small particles, which can effectively and flexibly adapt to the market demand for high energy efficiency, high gram capacity, and high energy efficiency energy storage.

[0061] The mass ratio of the small-particle lithium iron phosphate positive electrode material to the positive electrode active material of the battery is 5% to 50%.

[0062] In a fourth aspect of the present invention, a secondary battery is provided, comprising a separator, a negative electrode sheet, an electrolyte, a battery casing and the positive electrode sheet mentioned above.

[0063] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer can be one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium.

[0064] Among them, graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds, silicon carbon composites, and silicon alloys; tin-based materials can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be any material suitable for use as a negative electrode current collector for secondary batteries in the art. For example, the negative electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to copper foil.

[0065] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0066] The present invention will be further described below by means of specific examples.

[0067] Example 1

[0068] Preparation of lithium iron phosphate positive electrode material:

[0069] Step 1: Add high polyphosphoric acid and fatty alcohol ether polyoxyethylene ether into a reactor and mix well, and react at 80°C for 3 hours to obtain fatty alcohol polyoxyethylene ether phosphate as a carbon source, wherein the molar ratio of phosphorus in the high polyphosphoric acid to iron in the iron phosphate in step 2 is 1:100, the degree of polymerization of the high polyphosphoric acid is 4, and the number of carbon atoms in the carbon chain of the fatty alcohol polyoxyethylene ether is 12.

[0070] Step 2: prepare iron phosphate with an iron-phosphorus molar ratio of 0.983, and the molar ratio of lithium in lithium carbonate to iron in iron phosphate is 1.028:1; the amount of carbon source added is 12% of the mass of iron phosphate; the metal compound is titanium dioxide, and the amount of metal compound is 1.5% of the mass of iron phosphate; the conductive agent is selected as nano-carbon tubes, and the amount is 1.5% of the mass of iron phosphate; the above-mentioned iron phosphate, lithium carbonate, carbon source, titanium dioxide and nano-carbon tubes are poured into a ball mill, pure water is added, the solid content is 30%, and ball milling is carried out, and the ball milling particle size is controlled at D50 of 0.3 microns to obtain a mixed slurry.

[0071] Step 3: Spray dry the mixed slurry, the spray pressure is 4MPa, the inlet temperature of the spray dryer is 260℃, the outlet temperature is 110℃, and after the temperature is qualified, spray granulation is performed. The precursor obtained after spray drying is sintered under nitrogen. The sintering furnace environment requires that the oxygen content in the nitrogen is less than 20ppm and is isolated from the outside air. The loading thickness of the precursor in the sagger is 3cm. The total sintering time is 15 hours. Specifically, the precursor is heated to 730℃ for 6 hours, then kept at this temperature for 9 hours, then cooled, and the temperature is lowered to below 50℃ for discharge. Finally, the sintered material is sieved and airflow crushed in a constant temperature and humidity room. The temperature of the constant temperature and humidity room is 20℃, the relative humidity is 4%, and the sieve mesh is 400 to obtain lithium iron phosphate positive electrode material.

[0072] Preparation of secondary batteries:

[0073] The negative electrode sheet, the positive electrode sheet and the separator are interlaced and then packaged with an aluminum-plastic film to prepare a battery cell, which is placed in a battery shell, an electrolyte is added, and then sealed to obtain a lithium-ion battery. The active material of the negative electrode sheet is graphite; the active material of the positive electrode sheet is the above-mentioned lithium iron phosphate positive electrode material.

[0074] Example 8

[0075] Different from Example 1, the active material of the positive electrode sheet includes the lithium iron phosphate positive electrode material of Example 1 and a conventional high-density lithium iron phosphate material; wherein the conventional high-density lithium iron phosphate material is a conventional commercially available material, and the powder compaction is 2.50 g / cc. The lithium iron phosphate positive electrode material and the conventional high-density lithium iron phosphate material are mixed at a mass ratio of 1:4.

[0076] The rest is the same as Example 1 and will not be described again here.

[0077] Comparative Example 1

[0078] Different from Example 1, in step 2, fatty alcohol polyoxyethylene ether is used as the carbon source; in addition, diammonium phosphate, a phosphorus supplement, is added at a molar ratio of 1:100 between phosphorus in diammonium phosphate and iron in ferric phosphate.

[0079] The rest is the same as Example 1 and will not be described again here.

[0080] Comparative Example 2

[0081] Different from Comparative Example 1, the carbon source is glucose.

[0082] The rest is the same as that of Comparative Example 1 and will not be described again.

[0083] Comparative Example 3,

[0084] Different from Example 2, the active material of the positive electrode sheet is a conventional high-density lithium iron phosphate material, which is a conventional commercially available material.

[0085] The rest is the same as Example 2 and will not be described again here.

[0086] Among them, Table 1 shows the preparation parameters of the embodiments and comparative examples, and the remaining parameters are the same as those of Example 1 and will not be repeated here.

[0087] Table 1

[0088]

[0089] Performance Testing:

[0090] The lithium iron phosphate positive electrode materials of Examples 1 to 8 and Comparative Examples 1 to 9 were subjected to particle size test and powder compaction test, and the test results are shown in Table 2;

[0091] The lithium iron phosphate positive electrode material of Example 1 was tested by electron microscope. The test results are shown in Figure 1 .

[0092] The secondary batteries of Examples 1 to 8 and Comparative Examples 1 to 9 were subjected to electrochemical performance tests. The test results are shown in Table 2. Figure 2 ;

[0093] Table 2

[0094]

[0095]

[0096] As shown in Table 1 and Figure 2It can be seen from the test data shown that the particle size data of Examples 1 to 7 are smaller than those of Comparative Examples 1 to 3, indicating that the use of fatty alcohol polyoxyethylene ether phosphate as a carbon source in the present invention can produce a small-particle lithium iron phosphate positive electrode material, while after Comparative Examples 1 to 3 are separated from the carbon source system with a phosphorus supplement, the particles of Comparative Examples 2 and Comparative Example 2 grow significantly, the energy efficiency is relatively low, and the mixing value is lost.

[0097] Comparing the electrochemical performance data of Example 1 with that of Example 8, it can be seen that the electrochemical performance data of Example 8 is better than that of Example 1, indicating that the positive electrode active material of the battery formed by adding the small-particle lithium iron phosphate positive electrode material of the present invention to the conventional lithium iron phosphate positive electrode material can effectively form a large and small particle grading scheme with small particles as the main component, and can effectively and flexibly adapt to the market demand for high energy efficiency, high gram capacity, and high energy efficiency energy storage.

[0098] Compared with the electrochemical test data of Example 8 and Comparative Example 3, the electrochemical performance data of Example 8 are better than those of Comparative Example 3, indicating that the positive electrode active material of the battery formed by adding the small-particle lithium iron phosphate positive electrode material of the present invention to the conventional lithium iron phosphate positive electrode material can effectively form a large and small particle grading scheme with small particles as the main component, and can effectively and flexibly adapt to the market demand for high energy efficiency, high gram capacity, and high energy efficiency energy storage.

[0099] Comparison of the data of Examples 1 to 3 with Comparative Examples 4 to 5 shows that the data of Examples 1 to 3 are better than those of Comparative Examples 4 to 5. This is because a high degree of polymerization of polyphosphoric acid of 3 to 5 is beneficial to the improvement of the esterification rate, but too high a degree of polymerization reduces the consistency of the high degree of polymerization of polyphosphoric acid, thereby reducing the consistency of the esterification effect. Preferably, the degree of polymerization is 4.

[0100] By comparing the data of Examples 1, 4 and 5 with those of Comparative Examples 6 to 7, it can be seen that the data of Examples 1, 4 and 5 are better than those of Comparative Examples 6 to 7. The number of carbons in the carbon chain of fatty alcohol polyoxyethylene ether is related to the steric hindrance formed during the sintering process. When the number of carbons is 10 to 15, the steric hindrance provided during the sintering process can be effectively improved, and the growth of lithium iron phosphate primary particles can be effectively controlled, which is conducive to the realization of nano-sizing.

[0101] By comparing the data of Examples 1, 6 and 7 with those of Comparative Examples 8 to 9, it can be seen that the data of Examples 1, 4 and 5 are better than those of Comparative Examples 8 to 9, and the amount of carbon source used as a phosphorus supplement should not be too high; and a too low iron-phosphorus molar ratio may lead to excessive lithium phosphide and insufficient crystallinity of iron-lithium after sintering. Preferably, the iron-phosphorus molar ratio of iron phosphate and fatty alcohol polyoxyethylene ether phosphate is not less than 96%.

[0102] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: Step 1: Add high polyphosphoric acid and fatty alcohol ether polyoxyethylene ether into a reaction kettle and mix well, and react at 70-90° C. for 2-4 hours to obtain fatty alcohol polyoxyethylene ether phosphate; Step 2: adding iron phosphate, a lithium source, a conductive agent, a metal compound and the fatty alcohol polyoxyethylene ether phosphate into water for ball milling to form a mixed slurry; Step three: spray-drying, sintering and crushing the mixed slurry in sequence to obtain a lithium iron phosphate positive electrode material.

2. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1, the polymerization degree of the high polyphosphoric acid is 3 to 5.

3. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 1, the number of carbon atoms in the carbon chain of the fatty alcohol polyoxyethylene ether is 10-15.

4. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 2, the mass ratio of the fatty alcohol polyoxyethylene ether phosphate to the iron phosphate is 10-15%.

5. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: In step 2, the iron-phosphorus ratio of the ferric phosphate is 0.978-0.985, and the specific surface area is 10-15m 2 g -1 .

6. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the step 2, the particle size of the mixed slurry is 0.29-0.33 μm.

7. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the preparation method of the lithium iron phosphate positive electrode material according to any one of claims 1 to 6.

8. The lithium iron phosphate positive electrode material according to claim 7, characterized in that: It comprises a lithium iron phosphate matrix and a carbon coating layer coated on the surface of the lithium iron phosphate matrix, wherein the carbon coating layer accounts for 1.1-1.9% of the total mass of the lithium iron phosphate positive electrode material.

9. The lithium iron phosphate positive electrode material according to claim 7 or 8, characterized in that: The particle size D50 of the lithium iron phosphate positive electrode material is 0.2-0.45 μm.

10. The lithium iron phosphate positive electrode material according to claim 7 or 8, characterized in that: The specific surface area of ​​the lithium iron phosphate positive electrode material is 11 to 18 g / cm 2 .

Citation Information

Patent Citations

  • Preparation method of lithium iron phosphate material

    CN111129492A

  • Phosphoric milling agents and methods of use

    WO2024087057A1

Cited By

  • Preparation method of high-compaction-density lithium manganese iron phosphate positive electrode material

    CN120878808A

  • Preparation method of high-compaction-density lithium iron manganese phosphate positive electrode material

    CN120878808B